Antifungal Activity of Minocycline and Azoles Against Fluconazole-Resistant Candida Species - Tan, Jingwen; Jiang, Shaojie; Tan, Lihua; Shi, Haiyan; Yang, Lianjuan; Sun, Yi; Wang, Xiuli (Frontiers in Microbiology, 2021)
Candida species are the most common fungal pathogens to infect humans, and can cause life-threatening illnesses in individuals with compromised immune systems. Fluconazole (FLU) is the most frequently administered antifungal drug, but its therapeutic efficacy has been limited by the emergence of drug-resistant strains. When co-administered with minocycline (MIN), FLU can synergistically treat clinical C. albicans isolates in vitro and in vivo. However, there have been few reports regarding the synergistic efficacy of MIN and azoles when used to treat FLU-resistant Candida species, including C. auris. Herein, we conducted a microdilution assay wherein we found that MIN and POS showed the best in vitro synergy effect, functioning against 94% (29/31) of tested strains, whereas combinations of MIN+ITC, MIN+FLU, and MIN+VOR exhibited synergistic activity against 84% (26/31), 65% (20/31), and 45% (14/31) of tested strains, respectively. No antagonistic activity was observed for any of these combinations. In vivo experiments were conducted in Galleria mellonella, revealing that combination treatment with MIN and azoles improved survival rates of larvae infected with FLU-resistant Candida. Together, these results highlight MIN as a promising synergistic compound that can be used to improve the efficacy of azoles in the treatment of FLU-resistant Candida infections.